Immigrants facing Covid 19 containment in France : An ordinary hardship of disaffiliation - Séverine Carillon; Anne Gosselin; Karna Coulibaly; Valéry Ridde; Annabel Desgrées du Loû (Elsevier, 2020)
In order to limit the spread of the SARS-CoV-2 virus, the majority of governments have introduced population containment. Certain population groups, including immigrants in precarious situations, are experiencing the impact of this measure in a brutal manner. This article is based on accounts of containment experiences collected by telephone within the framework of a pre-existing intervention research carried out among immigrants to France from Sub-Saharan Africa who are in a precarious situation. It highlights certain social effects of containment and the logics at work in the precarious situations. This research shows how this a priori unprecedented situation affects individual capacities to act and generates a 'disaffiliation process' causing individuals to shift towards 'social non-existence', repeating lived experiences and exacerbating pre-existing logics. The ordeal of containment proves to be an ordinary experience for these individuals.